Edukasi Penggunaan Teknologi Dalam Menghadapi Tantangan Dan Solusi Problema Remaja Di Era Digital - Sri Restu Ningsih; Lise Asnur; Elizamiharti Elizamiharti; Defiariany Defiariany; Erdisna Erdisna; Weni Kurnia Sari; Febriyanno Suryana (Jurnal Pengabdian Masyarakat Dharma Andalas, 2026)
Teenagers in the digital era are often faced with phenomena such as gadget addiction, the spread of false information (hoaxes), cyberbullying, pressure to always appear perfect on social media, and the risk of exposure to negative content. Therefore, it is necessary to socialize among students at the Ramadhan Islamic Boarding School, on how to overcome these phenomena wisely. The purpose of this Community Service (PKM) is to provide education to provide solutions to adolescent problems in the digital era for students. This activity was carried out at the Ramadhan Islamic Boarding School, Al-Wustha Mosque, Padang City. The methods used in implementing this activity were lectures, question and answer methods, and quizzes. The material provided was education on how to overcome phenomena that often occur among students, especially teenagers, in the digital era, by understanding the positive and negative impacts and their effects on students. The result of this PKM activity was an increase in students' knowledge in overcoming phenomena that often occur among students in this digital era, as well as their positive and negative impacts on students